A lytic bacteriophage isolate reduced Clostridium perfringens induced lesions in necrotic enteritis challenged broilers - Keerqin, Chake; McGlashan, Katherine; Van, Thi Thu Hao; Chinivasagam, Helene N.; Moore, Robert J.; Choct, Mingan; Wu, Shu-Biao (Frontiers in Veterinary Science, 2022)
Background: Bacteriophages are viral predators of bacteria and occur commonly in nature. Their host-specific infections against specific bacteria make them an attractive natural agent to control bacterial pathogens. Interest in the potential of bacteriophages as antibacterial agents in the production animal industries has increased. Methods: A total of 18 bacteriophages were isolated from Australian commercial poultry environments, from which three highly active phages were chosen for enrichment. Sequencing libraries were prepared using a Nextera XT kit (Illumina) and sequenced on an Illumina MiSeq instrument using 2×300 bp paired-end chemistry. The sequence data were then assembled and aligned with a2 bacteriophage as the reference. An animal trial was performed by oral gavaging Clostridium perfringens netB containing strain EHE-NE18 to the Ross 308 broiler chickens prior inoculation with Eimeria species. The chickens were raised following the management guide for Ross 308 from d 0 to d 21 and fed with starter and grower diets met the specific breed nutrient requirements. Body weight gain and feed intake were measured on d 9 and d 21 and FCR adjusted with mortality was calculated. Results: The isolated bacteriophages only had only 96.7% similarity to the most closely related, previously characterised, Clostridium bacteriophage indicated that they might represent a novel strain of bacteriophage. A ‘cocktail’ containing the three bacteriophages was capable of lysing four known disease-inducing C. perfringens strains in vitro. Oral administration of the bacteriophages cocktail to broilers challenged with necrotic enteritis markedly alleviated intestinal necrotic lesions in the duodenum and jejunum on day 16. The phage treatment significantly reduced the lesion scores of birds challenged with NE (P < 0.01), and the lesion scores between birds treated with the bacteriophages and the control unchallenged birds were not statistically different (P > 0.05). However, no effect on the growth performance was apparent during the recorded period of days 9-21. Conclusions: These findings suggest that bacteriophage treatment is a promising approach to protect intestinal health from C. perfringens induced necrotic enteritis. Further research will be required on the dosing, route of administration, and large scale validation studies to further advance this approach to pathogen control.